Multitargeted therapy in the convergence era: Systems pharmacology, smart delivery, and the rise of pan-biomarkers - Munikumar Manne (Journal of Applied Pharmaceutical Science, 2025)
The landscape of therapeutic innovation is undergoing a profound transformation, driven by the convergence of systems pharmacology, smart drug-delivery platforms, and pan-biomarkers. This editorial explores the paradigm shift from organ-specific interventions to mechanism-guided, cross-disease strategies enabled by multi-targeted therapies. By integrating nanomedicine, AI-enhanced drug design, and precision-delivery systems, these approaches offer unprecedented potential to address complex, heterogeneous diseases. Through selected case studies in oncology, neurodegeneration, infectious diseases, and autoimmune disorders, we highlight the translational promise and clinical relevance of pan-target therapeutics. This commentary advocates regulatory reform, biomarker-driven stratification, and broader clinical adoption to fully realize the impact of these innovations in modern healthcare.
Keywords: Pan-target therapy, Systems pharmacology, Targeted drug delivery, Nanomedicine, Pan-biomarkers, Precision medicine, Cross-disease therapeutics